Consumer behavior in purchasing shopee online products: Literature review - irwandi, irwandi; Regina, Regina; Hasdiansa, Ilma Wulansari (Institute of Computer Science (IOCS), 2024)
This research was conducted to understand consumer behavior when purchasing goods online Shopee. Previous studies or significant research help to improve the theory and phenomenon of the relationship or influence of variables. The purpose of this study is to conduct a literature evaluation on consumer behavior when purchasing goods via the internet. This journal was written using a Library Research or Literature Review approach, including data from national and international sources. Using this approach, 12 journals were reviewed. The findings reveal that psychological, cultural, social, and personality aspects have a major impact on online consumer behavior. However, there are other factors that influence consumer behavior when buying products online, such as convenience factors, content, response, security, trust, experience, views of people nearby, perceived behavioral control, perceived benefits, lifestyle, information quality, price perception, risk perception, income, promotion, service, quality, rating, and ease of use of E-commerce. However, some journals reveal an insignificant relationship between consumer behavior and their decisions.